2023
DOI: 10.1155/2023/3327994
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Factors Affecting Use Behavior towards Mobile Payment Apps: A SEM Approach

Abstract: The main aim of this research study is to examine the impact of five independent variables viz. performance expectancy, effort expectancy, social influence, facilitating conditions, and hedonic motivation on behavioral intention to use mobile payment apps. This study is further aimed at investigating the influence of behavioral intention on the use behavior of mobile payment app users. This study strives to investigate the use behavior of people who have already used mobile payment apps like Google Pay, PhoneP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 71 publications
(113 reference statements)
0
5
0
Order By: Relevance
“…The influence of aesthetics on perceived usability has been a topic of interest in various fields such as computer science, business and psychology [144][145][146][147][148]. Several studies have emphasized the significant role of aesthetics in influencing perceived usability [87][88][89]. For example, aesthetics are important in supporting content and functionality, appealing to target audiences' tastes, creating necessary imagery and meeting the requirements of website types [149].…”
Section: Research Methods and Hypothesismentioning
confidence: 99%
See 1 more Smart Citation
“…The influence of aesthetics on perceived usability has been a topic of interest in various fields such as computer science, business and psychology [144][145][146][147][148]. Several studies have emphasized the significant role of aesthetics in influencing perceived usability [87][88][89]. For example, aesthetics are important in supporting content and functionality, appealing to target audiences' tastes, creating necessary imagery and meeting the requirements of website types [149].…”
Section: Research Methods and Hypothesismentioning
confidence: 99%
“…The intention to pay reflects users' assessment of the likelihood to purchase a technical application or service [85]. Multiple factors shape this intention to pay: content quality and interactive experience can heighten users' intention to pay in online entertainment [86]; trust, perceived benefits, risks and value are also vital antecedents [87,88]. Numerous studies have demonstrated that the willingness to use digital tools for payments is influenced by various factors.…”
Section: Intention To Paymentioning
confidence: 99%
“…The Unified Theory of Acceptance and Use of Technology (UTAUT) is a theory used to study changes in consumer attitudes toward digital payment methods (Istijanto and Handoko, 2022). According to Linge et al (2023), UTAUT is the most popular model or theory used to explain the adoption and usage of new technology by the general public. UTAUT serves as a framework to e-ISSN : 2716-4411…”
Section: Unified Theory Of Acceptance and Use Of Technology (Utaut)mentioning
confidence: 99%
“…On the other hand, perceived usefulness is defined as ''the consumer's perception of the superiority of digital payment systems in terms of speed, security and convenience'' (Linge et al, 2023). It relates to a service's or item's functional value (usefulness) in completing a task or achieving a goal.…”
Section: Hypotheses Formulationmentioning
confidence: 99%
“…Scholars stated that perceived usefulness is positively associated to technological readiness, specifically online learning readiness (Pham & Dau, 2022), wearable payment readiness (Lee et al, 2020), and readiness for a cashless society (Islam et al, 2023). It was an influential factor that positively influenced the mobile payment services' adoption (Bailey et al, 2022;Flavia´n et al, 2020;Haritha, 2023;Linge et al, 2023;Merhi et al, 2019;Rahardja et al, 2023;M. Rahman et al, 2020).…”
Section: Hypotheses Formulationmentioning
confidence: 99%